ANALISIS FAKTOR KEPEMIMPINAN KOMPENSASI DAN BUDAYA ORGANISASI TERHADAP PRODUKTIVITAS TENAGA KERJA PADA PT. INDUSTRI KARET DELI MEDAN - Oslen Simarmata; Syaad Afifuddin; E. Harso Kardhinata (Universitas Medan Area, 2018)
The aim of this research is to know factors that affect manpower productivity especially leadership factors, compensation factor and cultural organisation factor in PT.Industri Karet Deli Medan. Methode of determining magnitude sample is use Slovin method with asumsion of sampling error totalled 5%, so obtained sample 96 manpower person. Top of Form Result for these research with distribute quesioner to manpower to 96 sample and doing interview to company about output or product motor circle tire to last three months 2013 from January to March 2013 so obtained data skor and production data to analyzed. For all of result research had testing result all item score and total score said valid, and inter item reliabel score. Data distributed normally follow line diagonal, and does not occur mulikolinearity, and does not occur heterokedastisity. Leadership factor is real positif and influence significantly to the manpower productivity. By simultan with α=0,05 to test two sides become 0,025 achieved F counts = 20,438 with sig.= 0,000 < 0,025 alleged by significan so together influence leadership factor ( , compensation factor ( , and factor of organization culture ( have positive influence on manpower produktivity, and see coefficient determination shows that by simultan leadership factor, compensation and organisational culture have positip influence on manpower produktivity as big as 40% whereas waste him 60% more still influenced other factors that untested in perusal this research. Keywords : productivity, production factor, tomato, cabbage potatoes